Outlining three arguments for Rights of Antarctica - Baard, Patrik; Mancilla, Alejandra (The Polar Journal, 2024)
In this article, we investigate three arguments for Rights of Antarctica (RoA), understood as recognising the whole continent as a rights-holder with legal standing. For this, we draw inspiration from the Antarctica Declaration, a text developed by an interdisciplinary and international group of scholars and activists. We scrutinise three justifications that could potentially be used in support of RoA. First, we investigate whether arguments for Rights of Nature (RoN) elsewhere can support RoA. RoN has been accepted in several domestic legislations. Unfortunately, we discover important disanalogies between RoA and RoN, defeating the purpose of justifying RoA with reference to RoN. Second, we scrutinise potential arguments that focus on giving rights to specific Antarctic ecoregions or places. However, such arguments would only cover parts of the continent, thus going against the holistic approach of RoA, and they would require using a broader understanding of ?attachments? as grounds for justifying rights for parts of Antarctica. In contrast, we construct an argument for accepting RoA based on four components: (1) Antarctica?s intrinsic value, (2) wider forms of human attachments, (3) Antarctica?s substantial role as a global systemic resource, and (4) the fact that Antarctica is under recurrent and substantial threats. While none of these are individually sufficient for recognising RoA, they can jointly make RoA appropriate. We conclude that it remains an open question whether international law or, more specifically, the Antarctic Treaty, would be open to such conceptual and normative innovation, adopting a new paradigm in our treatment of the nonhuman natural world. At the same time, we hope to kickstart a discussion of what RoA would require and how it should relate more generally to RoN discourses.
Publisher: Routledge
Keywords: Antarktis; Antarktistraktaten; jus

Norway's path to the Antarctic Treaty - Jølle, Harald Dag (Fram forum, 2021)
Keywords: Antarktis; Antarktistraktaten 1959; Norge; ekspedisjoner; historie; hvalfangst; internasjonal; jus; politikk

Four principles to justify claims to jurisdiction and to natural resources in Antarctica - Mancilla, Alejandra (Yearbook of Polar Law, 2020)
Global pressure over Antarctic resources will mount in the course of the coming decades. Three factors are likely to motivate states to claim jurisdictional rights or rights to natural resources in Antarctica: climate change, dwindling natural resources in the rest of the world, and the fact that – by virtue of Article IV of the Antarctic Treaty – the question of sovereignty remains unresolved. It is high time to think about the moral dimensions that should shape Antarctic claims in the future. Is there any state or group of states more entitled than others to make such claims? What does sound management of natural resources require? How should environmental concerns factor into decisions about jurisdictional control and appropriation of natural resources? With these broad questions in the background, in this article I examine four principles of justice that figure prominently in current theories of territorial rights and rights over natural resources in political philosophy: connection, capacity, fair distribution, and need. I show how these principles have been used by states, alone or in tandem, to justify claims to jurisdiction and claims to natural resources in Antarctica. After pointing to their main strengths and weaknesses, I suggest that they may be necessary, but insufficient to build a just framework for jurisdiction and appropriation of resources in the White Continent.
Keywords: Antarktis; jus; politikk; ressurser

The moral limits of territorial claims in Antarctica - Mancilla, Alejandra (Ethics & International Affairs, 2018)
By virtue of the Antarctic Treaty, signed in 1959, the territorial claims to Antarctica of seven of the original signatories were held in abeyance or “frozen.” Considered by many as an exemplar of international law, the Antarctic Treaty System has come to be increasingly questioned, however, in a very much changed global scenario that presents new challenges to the governance of the White Continent. In this context, it is necessary to gain a clearer understanding of the moral weight of those initial claims, which stand (despite being frozen) as a cornerstone of the treaty. The aim of this article is to offer an appraisal of such claims, which may be divided into two main kinds: those grounded on some relevant link to the territory, and those grounded on official documents and geographical doctrines. After pointing to the limitations and challenges that they face, I conclude with some remarks about how this assessment ought to serve as a starting point to rethink the territorial status of Antarctica.
Keywords: Antarktis; historie; jus; politikk; ressurser

Forskrift om etablering, drift og bruk av jordstasjon for satellitt i Antarktis - Kommunaldepartementet (Lovdata, 2017)
Place: Oslo
Keywords: Dronning Maud Land; jus; kommunikasjon; teknologi

Inspeksjonsordningen under Antarktistraktaten - Bech, Jon (Polarboken, 2014)
Keywords: Antarktis; jus; politikk

Norske krav i Sørishavet - Utfordringer for Sjøforsvaret - Aase, Johnny Grøneng (Norsk Tidsskrift for Sjøvesen, 2013)
Norge gjorde i 2009 krav på økonomiske soner utenfor Bouvetøya og Dronning Maud Land. Slike krav fører i følge Lov om økonomiske soner med seg forpliktelser som over tid får konsekvenser for Sjøforsvaret. l den økonomiske sonen som ble erklært utenfor fastlands-Norge på 1970-tallet har det vært Kystvakten som har opprettholdt juridiksjon, overvåket miljøet og kontrollert fisket. Norske og utenlandsk fartøyer har alt begynt å fiske i norsk økonomisk sone utenfor Bouvetøya. Det foregår i dag en rivende utvikling av teknologi for gruvedrift på store havdyp. Statlige og kommersielle private aktører posisjonerer seg aktivt for å kunne utnytte naturressursene i Sørishavet. Denne forfatteren mener at det vil tvinge seg fram et behov for stedlig overvåkning, kontroll og miljøvern i de norske økonomiske sonene i Antarktis. Det eksisterer ingen robust søk- og redningstjeneste i Antarktis. Siden Norge har gjort territorielle krav har vi også en moralsk forpliktelse om å kunne komme skipbrudne og syke til unnsetning i disse områdene. Overvåkning og hevding av juridiksjon i slike store og fjerntliggende havområder vil bli komplisert og dyrt. Kystvakten har i dag verken fartøyer eller personell for å kunne utføre dette. Rundt 2020 vil de store kystvaktskipene Nordkapp, Senja og Andenes være rundt 40 år og nærme seg tidspunktet for utfasing. Klimaendringene fører til migrasjon av fisk nordover mot kaldere vann i Barentshavet, og det vil derfor bli behov for fiskeriinspeksjoner lenger nord enn i dag. Kystvakten trenger å anskaffe store erstatningsfartøy for Nordkapp-klassen, og ved prosjekteringen bør man ta høyde for at Norge også vil ha behov for en kystvaktkapasitet i Antarktis. For å redusere risikoen for over- eller feilinvesteringer vil jeg gjennomgå hvordan en allerede i dag kan benytte satellitter for å kartlegge skipstrafikken i de norske områdene i sør. Ut fra dette bakgrunnsmaterialet kan Forsvaret anslå hvor mange fartøyer som vil være nødvendig å ha i sør.
Publisher: Sjømilitære samfund
Keywords: Bouvetøya; Dronning Maud Land; Sørishavet; havrett; jus; miljøovervåking; miljøvern; naturressurser; økonomi

Forskrift om miljøvern og sikkerhet i Antarktis - miljødepartementet, Klima- og (Lovdata, 2013)
Volume: 2013-04-26-412 Place: Oslo
Keywords: Antarktis; Dronning Maud Land; forurensning; forvaltning; jus; miljøvern; naturvern

Forskrift om miljøvern og sikkerhet i Antarktis - Miljøverndepartementet (Justisdep., 2013)
Pages: 1144-1160 Volume: 412 Place: Oslo
Keywords: Antarktis; jus; miljøvern

Continental shelf submission of Norway : in respect of Bouvetøya and Dronning Maud Land : executive summary (Oljedirektoratet, 2009)
Keywords: Bouvetøya; Dronning Maud Land; internasjonal; jus; kontinentalsokkel; politikk

Suverenitet, jurisdiksjon og samarbeid: Antarktistraktaten – forutsetninger og innhold - Skagestad, Odd Gunnar (Norsk statsvitenskapelig tidsskrift, 2009)
Keywords: Antarktis; jus; politikk

Forskrift om grunnlinjen for sjøterritoriet ved Bouvetøya - Utenriksdepartementet (Lovdata, 2005)
Volume: 2005-02-25-174 Place: Oslo
Keywords: Bouvetøya; forvaltning; jus

The protocol on environmental protection to the Antarctic Treaty: a ten-year review - Vidas, Davor (Yearbook of international co-operation on environment and development, 2002)
Keywords: Antarktis; jus; miljøvern

Implementing the environmental protection regime for the antarctic - Vidas ed., Davor (Kluwer, 2000)
Publication Title: Environment & policy Issue: 28
Keywords: Antarktis; jus; miljøvern

The Southern Ocean seabed: arena for conflicting regimes? - Vidas, Davor (Order for the oceans at the turn of the century, 1999)
Keywords: Sørishavet; jus

Forskrift om regulering av fiske med norske fartøyer i Antarktis (CCAMLR-området) - fiskeridepartementet, Nærings- og (Lovdata, 1998)
Place: Oslo
Keywords: Sørishavet; fiskeri; jus

Forskrift om vern av miljøet i Antarktis - Miljøverndepartementet (1995)
Publisher: Lovdata Place: Oslo
Keywords: Antarktis; jus; miljøvern

The legitimacy of the Convention on the on the Regulation of Antarctic Mineral Resource Activities - Joyner, Christopher C (Fridtjof Nansens institutt, 1994)
Publication Title: IARP publication series
Keywords: Antarktis; jus; mineraler

The protocol on environmental protection to the Antarctic Treaty: the question of effectiveness - Orrego Vicuña, Francisco (Fridtjof Nansens institutt, 1994)
Publication Title: IARP publication series
Keywords: Antarktis; jus; miljøvern

The Antarctic Treaty system and Antarctic tourism: towards a legal regime? - Vidas, Davor (International Challenges, 1994)
Keywords: Antarktis; jus; turisme

Executive summary: International Antarctic Regime Project publication series 1993 (Fridtjof Nansens institutt, 1993)
Publication Title: IARP publication series
Keywords: Antarktis; jus; litteratur; politikk

The legitimacy of the Convention on the Conservation of Antarctic Marine Living Resources - Davis, Bruce W; Herr, Richard A (Fridtjof Nansens institutt, 1993)
Publication Title: IARP publication series
Keywords: Sørishavet; jus; miljøvern; politikk

The effectiveness of the Convention on the Conservation of Antarctic Marine Living Resources - Stokke, Olav Schram (Fridtjof Nansens institutt, 1993)
Publication Title: IARP publication series
Keywords: Antarktis; jus; miljøvern

Antarctic tourism: a challenge to the legitimacy of the Antarctic treaty system? - Vidas, Davor (German yearbook of international law, 1993)
Keywords: Antarktis; jus; turisme

The Antarctic Treaty System and Antarctic tourism: towards a legal regime? (background information paper) - Vidas, Davor (Fridtjof Nansens institutt, 1993)
Keywords: Antarktis; jus; politikk; turisme

The Antarctic Treaty System and the law of the sea: a new dimension introduced by the 1991 Madrid protocol - Vidas, Davor (Fridtjof Nansens institutt, 1993)
Publication Title: IARP publication series
Keywords: Antarktis; jus

The Antarctic Treaty system and the law of the sea. Review of Christopher C. Joyner: Antarctica and the law of the sea - Vidas, Davor (International Challenges, 1993)
Keywords: Sørishavet; jus; litteratur

Executive summary: November 1992 (Fridtjof Nansens institutt, 1992)
Publication Title: IARP publication series
Keywords: Antarktis; jus; litteratur; politikk

Antarctica and non-state actors: the question of legitimacy - Herr, Richard A; Davis, Bruce W (Fridtjof Nansens institutt, 1992)
Publication Title: IARP publication series
Keywords: Antarktis; jus; politikk

Negotiating the mineral regime in the Antarctic: a review - Mørkved, Berit (International Challenges, 1992)
Keywords: Antarktis; jus; mineraler; politikk

The protection of the Antarctic environment - Orrego Vicuña, Francisco (Fridtjof Nansens institutt, 1992)
Publication Title: IARP publication series
Keywords: Antarktis; jus; miljøvern

Domestic politics and non-state actors in the Antarctic Treaty System: towards a framework - Stokke, Olav Schram (Fridtjof Nansens institutt, 1992)
Publication Title: IARP publication series
Keywords: Antarktis; jus; politikk

Protecting the frozen south - Stokke, Olav Schram (Green globe yearbook, 1992)
Keywords: Antarktis; jus; miljøvern; politikk

The Eleventh Antarctic Treaty Consultative Meeting - Scully, Richard Tucker (International Challenges, 1991)
Keywords: Antarktis; jus; politikk

Conference report: preservation or exploitation - Stokke, Olav Schram (Marine Policy, 1991)
Keywords: Sørishavet; forvaltning; jus; politikk

Symposium report: "The Antarctic Treaty System in World Politics" - Stokke, Olav Schram (International Challenges, 1991)
Keywords: Antarktis; Sørishavet; forvaltning; jus; politikk

The resource conventions implemented: the consequences for the sovereignty issue - Beck, Peter J (International Challenges, 1990)
Keywords: Antarktis; jus; politikk

The legitimacy of the ATS - Jørgensen-Dahl, Arnfinn (International Challenges, 1990)
Keywords: Antarktis; jus; politikk

CRAMRA and other enviromental regimes in the ATS: how well does CRAMRA fit? - Kimball, Lee A (International Challenges, 1990)
Keywords: Antarktis; forvaltning; jus; miljøvern

Towards firmer institutionalization of the ATS? Future role of the consultative meeting and the issue of a permanent secretariat - Messer, Kurt (International Challenges, 1990)
Keywords: Antarktis; forvaltning; jus

The relationship between the ATS and the LOS convention of 1982 - Safronchuk, Vasiliy S (International Challenges, 1990)
Keywords: Antarktis; Sørishavet; havrett; jus; politikk

The relevance of the ATS as a model for international cooperation - Stokke, Olav Schram (International Challenges, 1990)
Keywords: Antarktis; jus; politikk

The unfinished task: CRAMRA and the question of liability - Wolfrum, Rüdiger (International Challenges, 1990)
Keywords: Antarktis; jus; mineraler

The relationship between science and politics in international management of marine living resources: the case of CCAMLR - Indreeide, Thor Vidar (International Challenges, 1989)
Keywords: Antarktis; Sørishavet; forvaltning; jus; politikk

The legitimacy of concluding an Antarctic mineral resources convention among the Atarctic Treaty parties - Sollie, Finn (Antarctic challenge III: conflicting interests, cooperation, environmental protection, economic development, 1988)
Keywords: Antarktis; jus; mineraler

The Antarctic scene: legal and political facts - Trolle-Andreson, Rolph (The Antarctic treaty regime : law, environment and resources, 1987)
Keywords: Antarktis; Antarktistraktaten 1959; internasjonal rett; jus

Ressursforvaltningen i Antarktis - konflikt eller samarbeid? - Antonsen, Per (Fridtjof Nansens institutt, 1984)
Publication Title: Fridtjof Nansens institutt. Studie R
Keywords: Antarktis; forvaltning; jus; ressurser

The Development of the Antarctic Treaty System - Sollie, Finn (Antarctic challenge: conflicting interests, cooperation, environmental protection, economic development, 1984)
Keywords: Antarktis; Antarktistraktaten; internasjonal; jus; polarforskning; samarbeid

The development of the Antarctic Treaty System: trends and issues - Sollie, Finn (Antarctic challenge: conflicting interests, cooperation, environmental protection, economic development, 1984)
Keywords: Antarktis; jus; politikk

Konvensjon om bevaring av marine levende ressurser i Antarktis = Convention on the Conservation of Antarctic Marine Living Resources (Lovdata, 1980)
Place: Oslo
Keywords: Sørishavet; forvaltning; jus; marinbiologi; miljøvern; naturvern

Trends and prospects for regimes for living and mineral resources in the Antarctic + discussion - Sollie, Finn (Law of the sea: neglected issues - proceedings, Law of the Sea Institute twelfth annual conference, October 23-26, 1978, The Hague, 1979)
Keywords: Antarktis; forvaltning; jus

Antarktis-traktaten, ressursene og utnyttelsen - Sollie, Finn (Stiftelsen, 1977)
Publication Title: Fridtjof Nansen-stiftelsen på Polhøgda. Studie AA:P
Keywords: Antarktis; jus; politikk; ressurser

Internasjonale konferanser - Hva har de ført til? - Kyst-Norge], [Aksjon; Brox, Ottar (Kampen om havet, 1974)
Keywords: Sørishavet; havrett; hvalfangst; hvalfangstkvoten; internasjonal; jus; pelagisk; politikk

Vitenskapelig utforskning som internasjonalt samarbeidsprosjekt i polarområdene - Skagestad, Odd Gunnar (Stiftelsen, 1974)
Publication Title: Fridtjof Nansen-stiftelsen på Polhøgda. Studie AA:S
Keywords: Antarktis; forskning; jus; politikk

Antarctic resources: report form the informal meeting of experts 30 May - 9 June 1973 (Antarctic resources, 1973)
Keywords: Antarktis; forskning; jus; politikk; ressurser

Moderne sydpolsproblemer - Hambro, Edvard (Samtiden, 1973)
Keywords: Antarktis; jus; politikk; økonomi

Hvem bestemmer hva i Antarktis? - Rey (Polarposten, 1973)
Keywords: Antarktis; jus; politikk

The duration of the Antarctic treaty: an analysis of the amendment and revision procedures in a political perspective - Sollie, Finn (Stiftelsen, 1973)
Publication Title: Fridtjof Nansen-stiftelsen på Polhøgda. Studie AA:P
Keywords: Antarktis; jus; politikk

Et nytt territorium åpnes : en studie av forhandlingene om kontinentalsokkelkonvensjonen av 1958 - Traavik, Kim (Fridtjof Nansen-Stiftelsen, 1973)
Publication Title: Arktis/Antarktisprosjektet Volume: 006
Keywords: Sørishavet; havrett; jus

Suverenitet og samarbeid: Antarktis i samarbeidets tegn - Hanevold, Truls (Fridtjof Nansen-Stiftelsen, 1971)
Publication Title: Arktis/Antarktisprosjektet
Keywords: Antarktis; jus; politikk

Forskrift om fredning av Bouvetøya med tilliggende territorialfarvann som naturreservat - miljødepartementet, Klima- og (Lovdata, 1971)
Volume: 1971-12-17-9 Place: Oslo
Keywords: Bouvetøya; jus; miljøvern; naturvern

Antarktistraktaten: en ny type internasjonal organisasjon - Engh, Ulf (Stiftelsen, 1970)
Publication Title: Fridtjof Nansen-stiftelsen på Polhøgda. Studie AA:P
Keywords: Antarktis; jus; politikk

De konsultative møter under Antarktistraktaten - Hanevold, Truls (Stiftelsen, 1970)
Publication Title: Fridtjof Nansen-stiftelsen på Polhøgda. Studie AA:P
Keywords: Antarktis; jus; politikk

Antarktistraktaten, territorialkravene, forskningssamarbeidet - Bolin, Fredrik Th. (Polarboken, 1968)
Keywords: Antarktis; forskning; jus; politikk

Folkerettslige spørsmål vedrørende suverenitetsspørsmål i Antarktis - Krogdahl, Trygve (Internasjonal politikk, 1968)
Keywords: Antarktis; jus; politikk

Antarktistraktaten = The Antarctic treaty - Utenriksdepartementet (Norges traktater, 1968)
Keywords: Antarktis; jus

Traktatsamling i folkerettens alminnelige del og internasjonale organisasjoner - Bache, Mette M; Heggemsnes, Jens B (Universitetsforlaget, 1963)
Keywords: Antarktis; Antarktistraktaten 1959; jus

Noteveksling mellom Norges regjering og Sør-Afrika-Sambandets regjering angående lån til Sør-Afrika-Sambandet av Norway Station beliggende i det norske biland Dronning Maud Land - Utenriksdepartementet (Statsrådsekretariatet, 1960)
Pages: 197-205 Place: Oslo
Keywords: Dronning Maud Land; jus; politikk; stasjoner

Den internasjonale regulering av hvalfangsten - Eckstrøm, Kåre (Polarboken, 1955)
Keywords: Sørishavet; hvalfangst; jus

Omkring konsesjonsordningen for den pelagiske hvalfangst = Concession arrangement for pelagic whaling - Knudtzon, Hans Thomas (Norsk polar-tidende, 1951)
Keywords: Sørishavet; hvalfangst; jus

De l'acquisition de souveraineté sur les territoires polaires - Smedal, Gustav; Rokseth, Pierre (Librairie Arthur Rousseau, 1932)
Keywords: Antarktis; internasjonal; jus; polarområdene; politikk

Erwerb von Staatshoheit über Polargebiete - Smedal, Gustav (Gräfe und Unzer, 1931)
Publication Title: Öffentlich-rechtliche Vorträge und Schriften
Keywords: Antarktis; internasjonal; jus; polarområdene; politikk

Lov om Bouvet-øya, Peter I's øy og Dronning Maud Land m.m. (bilandsloven) (Lovdata, 1930)
Volume: 1930-02-27-3 Place: Oslo
Keywords: Bouvetøya; Dronning Maud Land; Peter I. Øy; jus; lovgivning

Forskrift om Bouvet-øya - Justisdepartementet (Lovdata, 1930)
Volume: 1930-09-19-3663 Place: Oslo
Keywords: Bouvetøya; jus

Erhvervelse av statshøihet over polarområder - Smedal, Gustav (Gyldendal, 1930)
Publication Title: Universitetet i Oslo. Det juridiske fakultet Volume: (dr. juris)
Keywords: Antarktis; internasjonal; jus; polarområdene; politikk

Anneksjonen av Bouvetøya i folkerettslig belysning - Ræstad, Arnold (Tidsskrift for retsvidenskap, 1929)
Keywords: Bouvetøya; jus